THE ROLE OF BIOMASS IN THE BIOECONOMIC POLICY OF UKRAINE AND ITS LEGAL REGULATION - Kucher, Oleg; Butorina, Veronika; Pustova, Natalia; Pustova, Zoia; Tkach, Oleh (Proceedings of the International Scientific Conference "Economic Sciences for Agribusiness and Rural Economy", 2021)
The article examines the need and possibility of introducing bioeconomy in the management system of the national economy, in the context of the focus on sustainable development through the use of the most modern techniques and technologies for the use of biomass. It is determined that the key role in the development of a new direction of the country's economy is played by the agricultural sector, as the bioeconomy of agricultural systems is based on agricultural biomass and biotechnology. Optimization of agricultural biomass flows is one of the components of bioeconomy development. It is noted that, given the significant natural and economic, raw material research and production potential and state support, Ukraine has great opportunities for bioeconomy development based on the production of environmentally friendly bioenergy products through the efficient use of agricultural biomass. The legal bases of the state management of the bioeconomic development of Ukraine are stated.